Several aspects of descriptive epidemiology of hematological malignancies in adult population of Ukraine, Belarus and Russian Federation after Chornobyl accident - Guslitser, L.N.; Zavelevich, M.P.; Koval, S.V.; Gluzman, D.F. (Experimental Oncology, 2016)
Chornobyl impact on the health of adult population in Ukraine, Belarus and Russian Federation was a subject of several studies. However, the studies of the effects of Chornobyl on leukemia in adult populations in post-Soviet countries are scarce and the results are contradictory up to present. The results of the epidemiological studies of the oncohematological consequences of Chornobyl accident are briefly reviewed with particular focus on pre-Chornobyl and post-Chornobyl trends in leukemia incidence in Ukraine, Belarus and Russian Federation as well as in small territories of these countries with various levels of radionuclide contamination. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.